Long-Term Hydraulic Conductivity of a Bentonite-Polymer Composite Permeated with Aggressive Inorganic Solutions - Scalia, Joseph; Benson, Craig H; Bohnhoff, Gretchen L; Edil, Tuncer B; Shackelford, Charles D (Journal of geotechnical and geoenvironmental engineering, 2014)
AbstractBentonite was modified to prevent alterations in hydraulic conductivity when permeated with aggressive inorganic solutions. Acrylic acid within bentonite slurry was polymerized to create a bentonite-polymer composite (BPC). Tests indicate that BPC generally swells more and retains low hydraulic conductivity compared with natural sodium bentonite (Na-bentonite) when contacted with aggressive inorganic solutions. BPC in deionized water swelled greater than 3.8 times the swell of the Na-bentonite used to create BPC (73 versus 19 mL/2 g). In 500 mM CaCl2, however, swell of BPC was similar to swell of calcium bentonite (<10 mL/2 g). Thin layers of BPC simulating geosynthetic clay liners were permeated directly with 5–500 mM calcium chloride (CaCl2) solutions and extreme pH solutions (1 M NaOH with pH 13.1, 1 M HNO3 with pH 0.3). BPC maintained low hydraulic conductivity (<8×10−11 m/s) for all solutions for the duration of testing (>2 years). In contrast, Na-bentonite and superabsorbent polymer (similar to the polymer in BPC) permeated with the same solutions had hydraulic conductivities at least three orders of magnitude higher (except for 5 mM CaCl2). Hydraulic conductivity of BPC does not follow the classical hydraulic conductivity-swell relationship typical of Na-bentonite. BPC eluted polymer during permeation but maintained low hydraulic conductivity. Polymer elution was lower in more concentrated CaCl2 solutions.